Ein Kalorimeter zur Bestimmung von Mischungsenthalpie - Mischungsenthalpien des binären Systems n-Hexan + Cyclohexan bei 25° - Hans Arm; Peter Bucher (CHIMIA)
A calorimeter for measuring enthalpies of mixing is described. Results of measurements for the system n-hexane + cylo-hexane at 25 °C are presented and compared with values from the literature.